The effect of different media conditions on production of fungal metabolites by aquatic fungi / Faizatul Iman Makpol - Makpol, Faizatul Iman (2014)
The discovery of beneficial compounds in many types of fungi especially freshwater fungi past years ago have initiated a new and very promising field in this research. Based on presence and absence data for a large number and variety of aquatic habits, it is about 3000 fungal species have been reported from aquatic habitat. The biodiversity, physiology, behavior, and secondary metabolite production of aquatic fungi occur differently in different conditions.. Freshwater chemical ecology nowadays integrated into a broader and more complex framework that includes aspects physiological, population, community, and even ecosystem ecology. Chemical defenses can vary dramatically among geographic regions, habitats, individuals within a local habitat, and within different portions of the same individual. Factors affecting this variance are poorly known, but include physical stresses and induction due to previous attack. A wide range of media are used for isolation of different groups of fungi that influence the vegetative growth and colony morphology, pigmentation and sporulation depending upon the composition of specific culture medium, pH, temperature, light, water availability and surrounding atmospheric gas mixture.